High Interobserver Agreement on PSMA PET/CT Even in the Absence of Clinical Data. (10th March 2023) - Bundschuh, Ralph A.; Lütje, Susanne; Bundschuh, Lena; Lapa, Constantin; Higuchi, Takahiro; Hartrampf, Philipp E.; Gorin, Michael A.; Kosmala, Aleksander; Buck, Andreas K.; Pomper, Martin G.; Rowe, Steven P.; Essler, Markus; et al.
Abstract : Background: Recommended by current guidelines, prostate-specific membrane antigen (PSMA)–directed PET/CT is increasingly used in men with prostate cancer (PC). We aimed to provide concordance rates using the PSMA reporting and data system (RADS) for scan interpretation and also determine whether such agreement rates are affected by available patient characteristics at time of scan. Patients and Methods: Sixty men with PC, who all underwent 68 Ga-PSMA-11 PET/CT, were included. Three independent, experienced readers indicated general scan parameters (including overall scan result, organ or lymph node [LN] involvement, and appropriateness of radioligand therapy). Applying PSMA-RADS 1.0, observers also had to conduct RADS scoring on a target lesion (TL) and overall scan level. During the first read, observers were masked to all relevant clinical information, whereas on a second read, relevant patient characteristics were displayed, thereby allowing for determination of impact of available clinical information for scan interpretation. We used intraclass correlation coefficients (ICCs; with 95% confidence intervals [CIs]), which were then rated according to Cicchetti (0.4–0.59 fair, 0.6–0.74 good, and 0.75–1 excellent agreement). Results: For general parameters, agreement rates were excellent, including an overall scan result (ICC, 0.85; 95% CI, 0.76–0.90), LN metastases (ICC, 0.89; 95% CI, 0.83–0.93), organ involvement (ICC, 0.82; 95% CI, 0.72–0.89), and indication for radioligand therapy (ICC, 0.94; 95% CI, 0.90–0.96). Overall RADS scoring was also excellent with an ICC of 0.91 (95% CI, 0.96–09.4). On a TL-based level, 251 different lesions were selected by the 3 observers (with 73 chosen by all 3 readers). RADS-based concordance rates were fair to excellent: all lesions, ICC of 0.78 (95% CI, 0.67–0.85); LN, ICC of 0.81 (95% CI, 0.63–0.92); skeleton, ICC of 0.55 (95% CI, 0–0.84); and prostate, ICC of 0.48 (95% CI, 0.17–0.78). When performing a second read displaying patient's characteristics, there were only minor modifications to the previously applied RADS scoring on a TL-based level (overall, n = 8): each reader 1 and 2 in 3/60 (5%) instances, and reader 3 in 2/60 (3.3%) instances. The main reason for recategorization (mainly upstaging) was provided information on PSA levels (4/8, 50%). Conclusions: Applying PSMA-RADS, concordance rates were fair to excellent, whereas relevant modifications were rarely observed after providing clinical data. As such, even in the absence of patient information, standardized frameworks still provide guidance for reading PSMA PETs. Those findings may have implications for a high throughput in a busy PET practice, where patient details cannot always be retrieved at time of scan interpretation or in the context of clinical trials or central reviews in which readers may be blinded to clinical data.